2017
DOI: 10.1007/s10753-017-0645-y
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Attenuates Pain Hypersensitivity and Decreases Astrocyte-Mediated Spinal Neuroinflammation in a Rat Model of Oxaliplatin-Induced Pain

Abstract: Neuroinflammatory response in spinal dorsal horn has been demonstrated to be a critical factor in oxaliplatin-induced pain. Melatonin has been shown to have anti-inflammatory and anti-allodynia effects in both preclinical and clinical studies. In the present study, we investigated the role of systemic administration of melatonin on oxaliplatin-induced pain. Intraperitoneal (i.p.) injection with oxaliplatin induced significantly mechanical allodynia and thermal hyperalgesia. Melatonin (i.p.) significantly allev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…Recent animal studies on neuropathic pain, fibromyalgia, orofacial pain, and allodynia (painful sensation caused by an innocuous stimulus) have also documented the analgesic effects of melatonin. [ 69 – 74 ] Such studies indicate that melatonin could reduce inflammatory and oxidative stress by modulating the nitroxidergic system. Lin et al (2017) have identified MT2 melatonin receptors in the dorsal root ganglia as being involved in the melatonin analgesic effect on neuropathic pain.…”
Section: Sensory Processing Dysfunctionmentioning
confidence: 99%
“…Recent animal studies on neuropathic pain, fibromyalgia, orofacial pain, and allodynia (painful sensation caused by an innocuous stimulus) have also documented the analgesic effects of melatonin. [ 69 – 74 ] Such studies indicate that melatonin could reduce inflammatory and oxidative stress by modulating the nitroxidergic system. Lin et al (2017) have identified MT2 melatonin receptors in the dorsal root ganglia as being involved in the melatonin analgesic effect on neuropathic pain.…”
Section: Sensory Processing Dysfunctionmentioning
confidence: 99%
“…Moreover, Veneroso et al reported that melatonin reduced cardiac inflammatory injury induced by acute exercise by decreasing the mRNA levels of IL-1, IL-6 and TNF-α [ 7 ]. Similar effects of melatonin on interleukin levels in models of heat stroke, acute liver injuries, and neuroinflammation induced by methamphetamine- and oxaliplatin-induced pain, have been observed [ 8 , 9 , 10 , 15 , 16 ]. The other sites in which anti-inflammatory properties of melatonin were observed include renal, pancreatic, and even retinal tissue [ 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 62%
“…Paclitaxel leads to increased expression of this chemokine and its receptor, CCR2, in DRG in a paclitaxel model of CIPN [99], and neutralizing MCP-1/CCL-2 in DRG blocked macrophage infiltration and subsequent hyperalgesia in a paclitaxel rodent model of CIPN [128]. Oxaliplatin is also capable of increasing MCP-1/CCL-2, primarily released from astrocytes, at the time that hyperalgesia is occurring in rats; a finding that was decreased by treatment with melatonin [129]. Melatonin may further protect against oxaliplatin-induced CIPN by preventing mitochondrial dysfunction and eventual neuronal apoptosis, as was evidenced in a recent extensive study using a combination of in vitro and in vivo methods in human tissue and behavioral assessments in rats exposed to paclitaxel [130].…”
Section: Neuronal and Glial Cell Mediators: Cytokines Chemokines And Thementioning
confidence: 96%